Toward a precision behavioral medicine approach to addressing high-risk sun exposure: a qualitative analysis. Issue 4 (16th September 2019) - Stump, Tammy K; Spring, Bonnie; Marchese, Sara Hoffman; Alshurafa, Nabil; Robinson, June K
Abstract: Objectives: Precision behavioral medicine techniques integrating wearable ultraviolet radiation (UVR) sensors may help individuals avoid sun exposure that places them at-risk for skin cancer. As a preliminary step in our patient-centered process of developing a just-in-time adaptive intervention, this study evaluated reactions and preferences to UVR sensors among melanoma survivors. Materials and Methods: Early stage adult melanoma survivors were recruited for a focus group ( n = 11) or 10-day observational study, which included daily wearing a UVR sensor and sun exposure surveys ( n = 39). Both the focus group moderator guide and observational study exit interviews included questions on UVR sensing as a potential intervention strategy. These responses were transcribed and coded using an inductive strategy. Results: Most observational study participants (84.6%) said they would find information provided by UVR sensors to be useful to help them learn about how specific conditions (eg, clouds, location) impact sun exposure and provide in-the-moment alerts. Focus group participants expressed enthusiasm for UVR information and identified preferred qualities of a UVR sensor, such as small size and integration with other devices. Participants in both studies indicated concern that UVR feedback may be difficult to interpret and some expressed that a UVR sensor may not be convenient or desirable to wear in daily life. Discussion: Melanoma survivors believe that personalized UVR exposure information could improve their sun protection and want this information delivered in a method that is meaningful and actionable. Conclusion: UVR sensing is a promising component of a precision behavioral medicine strategy to reduce skin cancer risk.